(untitled) (Fiep Bulletin - online, 2013)
In view of the limited number of papers that deal with the experiences of people related to body manifestations, specifically in the area of physiotherapy, this research, aimed at assessing the understanding of the physiotherapist on the corporeality and the body language evident in the customer served in sessions of physiotherapy. When considering the perception of the physiotherapist in relation to the body of the client, I refer to Maurice Merleau-Ponty, french philosopher who studies the corporeality, language and the language of the body with a phenomenological approach. The phenomenology is a theoretical and philosophical and also methodological line, that, in the present study, was explored in both theoretical questions, as in the analysis of testimonies. There were interviews with 12 physiotherapists, who has used the guiding question - "What is your understanding regarding the client’s body during the physiotherapeutic treatment?" - The testimonies obtained as a response could be analyzed through the comprehensive interpretation in order to illuminate the phenomenon being studied. With this research it was possible to reflect on the meaning of the body for the physiotherapist. Body as language, means of communication and body as corporeality, a physical body, psychological, social and cultural, seen in its completeness. The function of teaching was also emphasized, showing the concern of the physiotherapist with the student’s learning about the corporeality. Thus, this study may provide support to physiotherapists and other health professionals, for an understanding of the body manifestations and, as appropriate, also better understand the reality that involves assistance in health, providing a more efficient recovery of the disease of the person, which appears to receive care.